Characteristics associated with high levels of patient-reported adherence to self-management strategies prescribed by physiotherapists. (2nd January 2020) - Peek, Kerry; Carey, Mariko; Mackenzie, Lisa; Sanson-Fisher, Robert
Abstract : Background/aims: Physiotherapist-prescribed self-management strategies are an important component of physiotherapy practice but they can only be effective if patients adhere. The aim of this study was to explore patient-reported adherence to physiotherapist-prescribed self-management strategies, and the extent to which patient, physiotherapist, consultation and prescription characteristics are associated with high levels of adherence. Methods: A cross-sectional observational study across four private practices; including 14 physiotherapists and 113 patients was conducted. Data were collected in two stages. The first stage consisted of observing a patient at their physiotherapist consultation to collect data regarding the physiotherapist's prescription of self-management strategies. The second stage consisted of a follow-up telephone interview with each observed patient to record the patient-reported level of adherence to each prescribed self-management strategy. Results: Prescribed self-management strategies where physiotherapists asked patients to repeat details of the self-management strategy were 6.54 times (95% confidence interval 2.91–14.98) more likely to be highly adhered to than strategies where the physiotherapist did not do this. Prescribed strategies accompanied by printed information were 2.73 times (95% confidence interval 1.24–6.00) more likely to be highly adhered to than strategies that were not. Advice such as to rest from activity (odds ratio=0.18; 95% confidence interval 0.08–0.40) was less likely to be highly adhered to when compared to home-based exercise programmes. Conclusions: To improve patient-reported adherence to self-management strategies, physiotherapists should be encouraged to provide supplementary printed information and ask their patients to repeat details of the prescribed strategy.